The school counselor as consultant : an integrated model for school-based consultation - Parsons, Richard D.; Kahn, Wallace J. (Southbank, Victoria, Australia : Belmont, CA : Thomson/Brooks/Cole, 2005)
This unique text articulates a solution-focused, collaborative model of consultation that operates within a systems view of a school. This model allows counselors to conceptualize and employ a number of interventions, from those that take place at the level of a single student to those addressing the expanse of the community at large. In addition to its unique integrative model, the text distinguishes itself from others in its pedagogical approach. This book blends theory with practice and provides students with the tools to apply concepts through the use of practice exercises, case simulations and illustrations.
Includes bibliographical references and index.
Keywords: Educational counseling